Cortisol and Inflammatory Processes in Ovarian Cancer Patients Following Primary Treatment: Relationships with Depression, Fatigue, and Disability - Schrepf, Andrew (2012)
Elevations in the pro-inflammatory cytokine interleukin-6 (IL-6) and alterations in the anti-inflammatory hormone cortisol have been reported in a variety of cancers. IL-6 has prognostic significance in ovarian cancer and cortisol has been associated with fatigue, disability, and vegetative depression in ovarian cancer patients prior to surgery. Ovarian cancer patients undergoing primary treatment completed psychological self-report measures and collected salivary cortisol and plasma IL-6 prior to surgery, at six months, and at one year. Patients included in this study had completed chemotherapy and had no evidence of disease recurrence. At six months, patients showed significant reductions in nocturnal cortisol secretion, plasma IL-6, and a more normalized diurnal cortisol rhythm, changes that were maintained at one year. The reductions in IL-6 and nocturnal cortisol were associated with declines in self-reported fatigue, vegetative depression, and disability. These findings suggest that primary treatment for ovarian cancer reduces the inflammatory response. Moreover, patients who have not developed recurrent disease by one year appear to maintain more normalized levels of cortisol and IL-6. Improvement in fatigue and vegetative depression is associated with the normalization of IL-6 and cortisol, a pattern which may be relevant for improvements in overall quality of life for ovarian cancer patients.